The persistence of informality: Evidence from panel data - Alpaslan Akay; Melanie Khamis (Institute for the Study of Labor (IZA), 2011)
Informality is a growing phenomenon in the developing and transition country labor market context. In particular, it is noticeable that working in an informal employment relationship is often not temporary. The degree of persistence of informality in the labor market might be due to different sources: structural state dependence due to past informality experiences and spurious state dependence due to time-invariant unobserved individual effects, which can alter the propensity of being in the informal sector independently from actual informality experiences. The purpose of our paper is to study the dynamics of informality using a genuine panel data set in the Ukrainian labor market. By estimating a dynamic panel data probit model with endogenous initial conditions, we find a highly significant degree of persistence due to previous informality experiences. This result implies that policies attempting to reduce current levels of informality may have a long-lasting effect on the labor market.
urn:nbn:de:101:1-2012010913906
Keywords: D60; I31; 330; informality; unobserved heterogeneity; state dependence; transition countries; Informeller Sektor; Schwarzarbeit; Hysteresis; Übergangswirtschaft; Ukraine